Multi-level analysis applications in business studies - حمود سعد علي; حسين عامر علي (Journal of Economics and Administrative Sciences, 2012)
The current research aims to provide a conceptual and applied frame on the subject of multi- level analysis in the research of business administration. The research tries to address some of the problems that befall the preparation of research and studies at the Arab level and local level, where the unity of theory and measurement and analysis, as well as clarify the various types of conceptual constructs and give researchers the ability to distinguish different models related to the level of analysis. On the other hand, this research provides an example of applied research illustrates the multi- level analysis steps in the light of data collected in a previous study of (103) Faculty involved (446) individual.